Historical Hegemony or Warranted Adaptation? A Response to Smith - Gibson, Lindsay; Case, Roland (Canadian Journal of Education/Revue canadienne de l’éducation, 2017)
In his article “Methodologically Historicizing Social Studies Education: Curricular Filtering and Historical Thinking as Social Studies Thinking,” Bryan Smith draws attention to limitations and confusions in the social studies thinking framework introduced by the Ontario Ministry of Education (OME; 2013) in its latest Grade 1–8 social studies, geography, and history curriculum (pp. 58–60). Smith’s underlying concern is that the OME has employed a conception of historical thinking developed by Peter Seixas (2015) as the basis for a framework for thinking in social studies. Smith argues that minor linguistic changes to Seixas’s terminology mask the predominantly historical focus of OME’s framework. According to Smith (2017), the imposition of historical thinking concepts ignores the interdisciplinary nature of social studies by privileging historical methods of inquiry over the methodologies of other social studies disciplines (p. 1).